Clostridium bifermentans and C. subterminale are associated with kiwifruit vine decline, known as moria, in Italy. (12th March 2020) - Spigaglia, Patrizia; Barbanti, Fabrizio; Marocchi, Fabio; Mastroleo, Marco; Baretta, Marco; Ferrante, Patrizia; Caboni, Emilia; Lucioli, Simona; Scortichini, Marco
Abstract: Since 2012, a new pathogenic syndrome has frequently been observed in many areas of kiwifruit cultivation in Italy. The main symptoms include an initial withering of the leaves followed by a total and sudden collapse of plants, mainly occurring during summer. The withered leaves fall and the main and secondary feeder roots appear rotten, sometimes showing a reddish‐brown discoloration. The disease, that affects both the green and yellow‐fleshed cultivars, has been called kiwifruit vine decline and is locally known as moria . The syndrome has been found consistently associated with soil waterlogging, which frequently occurs either after the traditional agronomical practice of irrigating orchards through surface irrigation or after very heavy rainfall. So far, the role played by bacteria in this syndrome has not been investigated. In the present study, Clostridium spp. were isolated from both rotten roots and soils obtained from Italian kiwifruit orchards affected by the syndrome, indicating for the first time that anaerobic bacteria are able to cause damage to woody crops. C. bifermentans and C. subterminale incited symptoms in kiwifruit in both in vivo and in vitro pathogenicity tests. Soil waterlogging seems to potentially favour colonization of kiwifruit roots by anaerobic bacteria, probably because saturation of the soil can facilitate proliferation and persistence of these bacteria during long periods of the vegetative growth of the crop. The occurrence of anaerobic bacteria does not exclude the possibility that other microorganisms can play additional/synergic role(s) in causing the kiwifruit vine decline. Abstract : Pathogenicity assays indicated that C. bifermentans and C. subterminale could cause kiwifruit vine decline of Actinidia chinensis varieties in Italy. This is the first observation of association of anaerobic bacteria with damage to a woody crop.